Laboratory Experiments on Soil Stabilization to Enhance Strength Parameters for Road Pavement - Lindh Per; Lemenkova Polina (Transport and Telecommunication, 2023)
Clay soils can cause significant distress in road construction due to their low strength. Stabilizing such soil improve with binder agents prior to the geotechnical works can significantly its performance and ensure safety and stability of roads while exploitation. This research envisaged the use of five different binders (lime, energy fly ash, bio fly ash, slag, cement) as an additive stabilizing agents to improve the strength parameters of soil as required in engineering industry standards. The variations of strength was assessed using measurements of P-wave velocity of the elastic waves propagating through soil specimens stabilized by different combination of binders. Measurements were performed on 28th day of soil treatment. The best effects of added binders were noted in the following combinations: cement / energy fly ash / bio fly ash (P-waves >3100 m/s), followed by combination lime / energy fly ash / GGBFS (P-waves >2800 m/s) and cement / lime / energy fly ash (P-waves >2700 m/s). Adding lime is effective due to its fixation and chemical bond with particles. The study contributes to the industrial tests on soil strength for constructing roadbed.